Outcome of primary closure following carotid endarterectomy with a novel technique: An 8-year multicenter cohort study - Amir Ahmad Arabzadeh, MD; Mohammadreza Kalantarmotamedi, MD; Babak Sabet, MD; Niki Tadayon, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
This study evaluated the safety and efficacy of a novel primary closure technique in carotid endarterectomy compared with traditional methods. Conducted over 8 years at three university hospitals, this study included 184 patients. Early complications (8.7%) included hematoma, transient ischemic attack, myocardial infarction, stroke, and death. Late complications involved myocardial infarction, death, transient ischemic attack, stroke, and reintervention. The 1-year follow-up showed a significant (>70%) restenosis rate of only 1.9%. The novel technique in carotid endarterectomy seems to be a safe and effective alternative to patch angioplasty, offering advantages for selected patients. Further studies are required.